The 3 R's of leadership : risk, responsibility, and reliability - Huntsman, Jon M. (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Winners Never Cheat: Even in Difficult Times (ISBN: 9780137009039) by Jon M. Huntsman. Parents and employers who nurture, praise, and when necessary, discipline fairly, experience happier and more successful lives for themselves and those in their charge"--Resource description page.